The evaluation of the optic nerve in multiple sclerosis using MRI histogram analysis - Doğan, Adil; Baykara, Murat (My University, 2020)
Aim: Comparison of optic nerve with healthy subjects by MRI histogram analysis in patients with multiple sclerosis (MS).Material and Methods: A total of 78 patients with age range of 39 ms (18-54), 27 females, 12 males and 39 healthy age range (19-54),26 females and 13 males (control group) were included in the study. The right optic nerve in the MS and control group was includedin the study. ROI was placed on the optic nerve from the images and numerical data were obtained by histogram analysis. Numericaldata were loaded into MATLAB program.Results: Mean, standard deviation, minimum, maximum, median, variance and entropy values were significantly higher in MSpatients than control group(p<0.05). In MS patients, changes in tissue histology were detected in the optic nerve compared tohealthy individuals by mri histogram analysis without a visual change in the optic nerve.Conclusion: We think that the diagnosis of optic neuritis, which has an important role in disability in MS patients, will improve thequality of life of patients with early diagnosis and treatment by MRI histogram analysis of the optic nerve.
Keywords: Optik; Klinik Nöroloji; Nörolojik Bilimler; Radyoloji; Nükleer Tıp; Tıbbi Görüntüleme